PROSES BERPIKIR SISWA TUNANETRA DALAM MEMECAHKAN MASALAH KUBUS DAN BALOK KELAS IX DI SMPLB-A TAMAN PENDIDIKAN DAN ASUHAN JEMBER - Lesmana, Indra; Susanto, Susanto; Oktavianingtyas, Ervin (Kadikma, 2015)
Abstract. The sense of sight is very important for human to dalily activities. Learning process needs the sense of sight to recognize beginning of an object and stimulus but different with blind students just use their sense of touch. Therefore blind students using Braille in learning process. This research aims to describe the thinking process of grade nineth blind students in resolving problem cubes and block at SMPLB-A Wildlife Education and Upbringing Jember. Solving the problem is a crucial aspect in the learning process. Solving the problems in this research used Polya's steps such that understanding the problem, making a plan, carrying out a plan, and looking back at the completed solution. The instrument which is used in this research are mathematics problem solving test and in depth interview. Subjects in this research are all students of grade IX SMPLB-A which are two children totally blind. Based on the results of research that both subjects with disequilibrium, assimilation, accommodation and equilibrium when solve mathematics problems but, the emergence of disequilibrium, assimilation, accommodation and equilibrium on each different subjects. Keywords:Problem Solving, Thinking Process, Blind Student